2019
DOI: 10.1002/adem.201900609
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effect of Hot‐Rolling Reduction on the Mechanical Properties of In Situ Formed Aluminum–Magnesium–Silicon (Al‐Mg2Si) Composites

Abstract: The effects of hot rolling on the microstructure and mechanical properties of as‐cast Al‐15Mg2Si, Al‐20Mg2Si, and modified Al‐15Mg2Si in situ composites are studied. During rolling, the primary and eutectic Mg2Si particles undergo mechanical fragmentation and move along the rolling direction, which results in the enhancement of ductility of the composite compared to the as‐cast state. At high reductions in thickness, however, severely elongated grains and some cracks are observed in the matrix, which are relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…As shown in Figure 8(a,b), in the cast state, the addition of yttrium to the base composite considerably develops the tensile performance, so that the addition of 0.9 wt-% Y results in UTS enhancement (more than 33%) and improved elongation per cent (up to about 90%). Among the predominant reasons that explain the enhancement of the tensile properties, structural modifications such as the refinement of the secondary phases and dendritic structures and the conversion of phases with sharp edges to more spherical ones are very important [47]. The improvement of tensile properties in the cast state can be connected to the modifier's effects on the size and volume fraction of the secondary phases and the development of a uniform structure, as seen in Figure 5.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 8(a,b), in the cast state, the addition of yttrium to the base composite considerably develops the tensile performance, so that the addition of 0.9 wt-% Y results in UTS enhancement (more than 33%) and improved elongation per cent (up to about 90%). Among the predominant reasons that explain the enhancement of the tensile properties, structural modifications such as the refinement of the secondary phases and dendritic structures and the conversion of phases with sharp edges to more spherical ones are very important [47]. The improvement of tensile properties in the cast state can be connected to the modifier's effects on the size and volume fraction of the secondary phases and the development of a uniform structure, as seen in Figure 5.…”
Section: Resultsmentioning
confidence: 99%
“…At present, a variety of methods have been studied to improve the microstructure organization of metallic alloys including chemical modifiers, [ 8 ] mechanical methods, [ 9,10 ] and heat treatment. [ 11 ] Yadav et al [ 12 ] used the cooling slope casting technique to cast A319–4 wt%Mg 2 Si composites and found that Mg 2 Si particles were remarkably refined and uniformly dispersed in the matrix, which contributed to the improvement of mechanical properties including hardness and tensile strength.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] It is regarded as a promising candidate for fulfilling the demanding criteria for exceptional mechanical and tribological properties within the automotive and aviation industries. [7][8][9] Consequently, the composites can be a candidate material used in the manufacturing of various automotive parts, including pistons, cylinder liners, connecting rods, cylinder blocks, and brake drums/rotors that are subject to sliding wear with their counterbodies during operation. [10,11] Al-Mg 2 Si composites can be fabricated using either in situ or ex situ techniques.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4–6 ] It is regarded as a promising candidate for fulfilling the demanding criteria for exceptional mechanical and tribological properties within the automotive and aviation industries. [ 7–9 ]…”
Section: Introductionmentioning
confidence: 99%